“KILLING SOMEONE": GROUNDS FOR DEFENDING THE INSTITUTE OF THE JURY TRIAL (ESMAT Magazine, 2025)
The article examines homicide as a profound violation of humancoexistence, addressing its complex motivations. The Jury Court is presented as aspace that integrates law, morality, and public participation, lending solemnity to thejudgment of serious crimes. Its ritualistic structure balances the gravity of homicide withthe seriousness required to address its implications. Criticism of the jury often reflectsresistance to the decentralization of judicial power, yet its liturgy is essential for dealingwith the emotional complexity of crimes against life. The Jury Court is a pillar ofdemocracy and justice, harmonizing reason and emotion in cases of extreme gravity,and its preservation is crucial for maintaining trust in the judiciary system and socialorder.
Keywords: Homicide; Jury Court; Popular Sovereignty; Rite